PENGARUH PENGGUNAAN GADGET TERHADAP EMOSI DALAM MENGHAFAL AL QURAN PADA MAHASANTRI RUMAH TAHFIDZ AL-QUR’AN AMAL SYUHADA SURAKARTA - Abbas, Ngatmin; Jannah, Miftakhul; Ramdhani, Luthfiyah Miftahur; Maajida, Dini Luthfiyya; Sholihah, Hanifah Ash (STKIP Pesisir Selatan, 2025)
This study aims to analyze the influence of gadget usage on emotional development and the ability to memorize the Qur’an among students (mahasantri) at Rumah Tahfidz Al-Qur’an Amal Syuhada Surakarta in the 2024/2025 academic year. The primary research questions are: (1) Does gadget usage affect the emotional development of mahasantri? (2) Does emotional development affect their ability to memorize the Qur’an? and (3) Does emotional development mediate the relationship between gadget usage and Qur’an memorization ability? This research employed a quantitative approach with an associative causal design. The sample consisted of 14 mahasantri selected through purposive sampling. Data were collected through questionnaires, observation, and documentation, and analyzed using validity and reliability tests as well as path analysis with SPSS. The results show that gadget usage has a positive and significant influence on emotional development (β = 0.785; p < 0.05) and directly affects Qur’an memorization ability (β = 0.732; p < 0.05). Furthermore, emotional development significantly influences memorization ability (β = 0.648; p < 0.05) and acts as a mediating variable in the relationship between gadget usage and memorization performance. These findings indicate that well-managed and educational use of gadgets can support emotional stability and improve memorization outcomes.